Malignant potential of neuroendocrine microtumor of the pancreas harboring high-grade transformation: lesson learned from a patient with von Hippel-Lindau syndrome - Jongwon Lee; Kyung Jin Lee; Dae Wook Hwang; Seung-Mo Hong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Pancreatic neuroendocrine microtumor (PNEMT) is a neuroendocrine tumor (NET) < 0.5 cm in diameter, and it is considered benign. We report a PNEMT with high-grade transformation (HGT). A man in his 60s with von Hippel-Lindau syndrome underwent surgical resection of a NET. A second sub-centimeter nodule with a nodule-in-nodule pattern was discovered. The 0.4 cm outer nodule contained clear columnar cells with round nuclei and indistinct nucleoli, while the 0.1 cm inner nodule had eosinophilic cells with an increased nuclear to cytoplasmic ratio, vesicular nuclei, and prominent nucleoli. Tumor cells in the outer and inner nodules were synaptophysin and chromogranin positive. Only the inner nodule was p53 positive, while the outer nodule was exclusively positive for carbonic anhydrase 9 and vimentin. The Ki-67 labeling indices for the outer and inner nodules were 2.1% (grade 1) and 44.3% (grade 3), respectively. This nodule was determined to be a PNEMT with HGT. Our findings suggest that a PNEMT may not always be benign and can undergo HGT.